Hillsong’s Colour Sisterhood and Feminism within the Context of South Africa: A Critical Analysis - Boshoff, Lucia Lilleen (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.